Anacetrapib, but not evacetrapib, impairs endothelial function in CETP-transgenic mice in spite of marked HDL-C increase. (February 2017) - Simic, Branko; Mocharla, Pavani; Crucet, Margot; Osto, Elena; Kratzer, Adelheid; Stivala, Simona; Kühnast, Susan; Speer, Thimoteus; Doycheva, Petia; Princen, Hans M.; van der Hoorn, Jose W.; Jukema, J. Wouter; et al.
Abstract: Background and aims: High-density lipoprotein cholesterol (HDL-C) is inversely related to cardiovascular risk. HDL-C raising ester transfer protein (CETP) inhibitors, are novel therapeutics. We studied the effects of CETP inhibitors anacetrapib and evacetrapib on triglycerides, cholesterol and lipoproteins, cholesterol efflux, paraoxonase activity (PON-1), reactive oxygen species (ROS), and endothelial function in E3L and E3L.CETP mice. Methods: Triglycerides and cholesterol were measured at weeks 5, 14 and 21 in E3L.CETP mice on high cholesterol diet and treated with anacetrapib (3 mg/kg/day), evacetrapib (3 mg/kg/day) or placebo. Cholesterol efflux was assessed ex-vivo in mice treated with CETP inhibitors for 3 weeks on a normal chow diet. Endothelial function was analyzed at week 21 in isolated aortic rings, and serum lipoproteins assessed by fast-performance liquid chromatography. Results: Anacetrapib and evacetrapib increased HDL-C levels (5- and 3.4-fold, resp.) and reduced triglycerides (−39% vs. placebo, p = 0.0174). Total cholesterol levels were reduced only in anacetrapib-treated mice (−32%, p = 0.0386). Cholesterol efflux and PON-1 activity (+45% and +35% vs. control, p < 0.005, resp.) were increased, while aortic ROS production was reduced with evacetrapib (−49% vs. control, p = 0.020). Anacetrapib, but not evacetrapib, impaired endothelium dependent vasorelaxation ( p < 0.05). In contrast, no such effects were observed in E3L mice for all parameters tested. Conclusions: Notwithstanding a marked rise in HDL-C, evacetrapib did not improve endothelial function, while anacetrapib impaired it, suggesting that CETP inhibition does not provide vascular protection. Anacetrapib exerts unfavorable endothelial effects beyond CETP inhibition, which may explain the neutral results of large clinical trials in spite of increased HDL-C. Highlights: CETP inhibitors, anacetrapib and evacetrapib, increased HDL-C and reduced triglyceride levels in hyperlipidemic mice. Anacetrapib reduced cholesterol levels while evacetrapib increased cholesterol efflux and PON-1 activity and reduced ROS. Anacetrapib worsen endothelium-dependent acetylcholine-induced vasorelaxation while evacetrapib showed no effect. CETP inhibition lacks vascular protective effects and compromised vascular function may lead to more cardiovascular events.